Sepiolite Enfolded Sulfur/ZnO Binary Composite Cathode Material for Li-S Battery - Kalaiselvi, Chelladurai; Subadevi, Rengapillai; Wang, Fu-Ming; Sivakumar, Marimuthu (Frontiers in Materials, 2020)
Lithium-Sulfur (Li-S) batteries have turned into an incredible challenger for the succeeding age of high vitality stockpiling gadgets. Nevertheless, one of the real specialized issues emerging in Li-S battery is the polysulfide disintegration among electrodes and striking capacity limit. Here, sieved sepiolite (200 mesh sieve) has been favored as an added substance material to have the above difficulties in the sulfur battery. The zinc oxide nanoparticles were prepared by co-precipitation method and Sulfur/post-treated sieved Sepiolite/Zinc Oxide(S/PTSp/ZnO) nanocomposite has been prepared by warmth treatment. The prepared composite has been described by XRD, FTIR, RAMAN, SEM with EDAX, TEM, XPS, TG and Electrochemical analysis. The S/PTSp/ZnO composite cathode exhibits an initial discharge capacity of 1391 mAhg-1 and attains a stable capacity 765 mAhg-1 at 200 cycles. In the rundown, Li-S battery can be relied upon to capably build up the utilization of sulfur and limit the disintegration of polysulfides into an electrolyte.